Cluster：Theoretical Study on the Paramagnetic Properties of Cluster CrPS4 - LIU Li′e; FANG Zhigang; HOU Qianqian; L Mengna; ZHENG Xinxi; WANG Qian (Journal of Harbin University of Science and Technology)
In order to explore the paramagnetic properties of CrPS4 at a temperature of 298.15K, and to contribute theoretical basis for subsequent research and applications. The article is based on density functional theory, using B3LYP functional and def2-tzvp basis set, using Gaussian09 quantum chemistry software, through the analysis of the single electron number, spin population, density of states and electron spin density difference diagram of the 16 configurations of the cluster CrPS4.The conclusions are as follows: When the temperature is 298.15K, the magnetic moment of the cluster CrPS4 is positive, which is paramagnetic. The magnetism of the quadruplet state is better than that of the doublet state; for the s, d, and f orbitals, the single electrons are mostlyαelectrons with upward spin, and the relationship between the contribution rate to the magnetism is as follows: d orbital>s orbital>f orbital, and most p orbitals areβelectrons with downward spin, which has a weakening effect on the magnetism of the cluster; from the atomic point of view, the main source of magnetism is Cr, P、S can weaken the magnetism of cluster CrPS4, and different S have different weakening effects in the same configuration; the spin directions of electrons in both s orbital and p orbital have changed.